Integrating the individual and the organization - Argyris, Chris (Transaction Pub. New BrunswickUS, 1990)
Focuses on organizational change in corporate life. Discusses how individuals in organizations can become more effective, and consequently, enhance the effectiveness of their organizations. Explores and examines the negative consequences of the conventional pyramidal structure of organizations. Examines the characteristic learning system of modern organizations, and provides a summary view of the organization of the future.